IMPORTANCE OF PHILANTHROPIC MOVEMENT IN SOCIETY DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
This article reveals the socio-philosophical aspects of the fact that philanthropic activity is a universal phenomenon, that it manifests in a unique way in the lives of representatives of different peoples, different cultures and religious denominations. It is based on the views of Eastern and Western thinkers that the development of philanthropic activity in the development of society is based on its own stages. Philanthropic activity has its place in the development of society, and this process, as a charitable activity, has always been analyzed as a complex movement of the socio-economic process.